The Effect of Coenzyme Q10 on Vestibular Compensation Process after Unilateral Labyrinthectomy in Rats Using Behavioral Tests - Ayşe Çeçen; Rıfat Karlı; Asude Ünal (The Turkish Journal of Ear Nose and Throat)
Objective: To determine the effect of coenzyme Q10 on the vestibular compensation process after unilateral labyrinthectomy. Material and Methods: Thirty Wistar rats were randomly assigned to 3 equal groups: the negative control group, the experimental group and the control group. Labyrinthectomy surgeries were performed in all 3 groups. After the labyrinthectomy, findings such as nystagmus with its fast phase directed to the undamaged side, deviation of the head to the side operated on, impairment in walking, and decreased tonus of the extensor muscles on the same side were observed. Results: The values of Group EG and Group CG were somewhat higher than those of Group NCG in terms of the degree of head tilt, but there was no statistically significant difference among the three groups. Although Group EG and Group CG were found to differ statistically significantly from Group NCG on certain days in terms of postural deficit values and nystagmus, this significance remained limited to those particular days. Conclusion: The effect of CoQ10 on the vestibular compensation process was limited may be due to its limited dose, short duration of administration, and the limited number of rats. We believe that the effects of CoQ10 on the vestibular compensation process after labyrinthectomy should not be neglected. Despite the fact that we administered it at limited doses for a short term on a limited number of rats, CoQ10 should be used in larger samples, in higher doses, and for a longer time because CoQ10 has positive, though limited effects, on the vestibular compensation process.